Organizational Support in Career Self-Management: A Systematic Literature Review - Mariana Martins; Maria do Céu Taveira; Flávio Magalhães; Ana Daniela Silva (Administrative Sciences)
The present study consists of a systematic literature review, based on the PRISMA model, with the objective of analyzing the relationship between organizational support and career self-management in order to address the gaps in the existing literature. Specifically, it seeks to answer whether organizational support influences career self-management behaviors and whether the inverse also occurs. To systematize the scientific knowledge on this topic over the past 13 years (2010–2023), three databases were consulted: Web of Science, Scopus, and Core. This research resulted from the combination of the keywords “career self-management” and “organizational support: and involved the screening of 353 studies. For the systematic literature review, a total of six studies were identified that met the established eligibility criteria. The main conclusions of this study are that organizational support, in the form of perceived organizational support, human resource management practices/perception of human resource management practices, and leader–member exchanges, appears to positively influence career self-management, as well as the inverse. Such evidence can be observed through the direct and indirect relationships established between the variables. This relationship leads, for example, to workers being more satisfied with their careers while also becoming more committed to the organization. Overall, this systematic literature review provides practical implications for organizations and their workers. It is suggested that future research should explore the relationship between career self-management and organizational support, as well as other potential mediators of this relationship.